Hubungan antara Kualitas Tidur dan Kecemasan dengan Tekanan Darah Pasien Pre Operasi Vitrectomy di Ruang Baitul Izzah 2 RSI Sultan Agung Semarang - Windilla Windilla; Dwi Retno Sulistyaningsih; Erna Melastuti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Anxiety in patients undergoing preoperative vitrectomy can have a significant impact on biological, psychological, social, and spiritual aspects, manifesting as increased blood pressure, pulse rate, respiratory rate, and sleep quality disturbances that can affect physiological and psychological balance. Blood pressure is influenced by the autonomic nervous system, making anxiety and sleep quality important factors related to cardiovascular stability. This study aims to explain the relationship between sleep quality and anxiety with blood pressure in preoperative vitrectomy patients. The research design used was a cross-sectional correlation study involving 108 respondents. The instruments used included the Pittsburgh Sleep Quality Index (PSQI) to assess sleep quality, the Zung Self-Rating Anxiety Scale (ZSAS) to assess anxiety, and blood pressure measurements before surgery. The analysis used the Spearman test. The results showed that most respondents were in the early elderly age category (34.3%), had a high school education (54.6%), and were employed (57.4%). Most experienced mild sleep disturbances (81.5%) and mild anxiety. The average systolic blood pressure of respondents was 133.50 mmHg (SD 11.569) and diastolic blood pressure was 84.29 mmHg (SD 11.081). Spearman's test showed a relationship between sleep quality and systolic blood pressure (r=0.237; p=0.014) and diastolic blood pressure (r=0.428; p=0.001), as well as between anxiety and systolic blood pressure (r=0.502; p=0.001) and diastolic blood pressure (r=0.326; p=0.001). It was concluded that there was a relationship between sleep quality and anxiety with the blood pressure of patients undergoing preoperative vitrectomy. Nurses are advised to conduct early screening and simple interventions to reduce anxiety and improve the sleep quality of patients